Application of Lactic Acid Bacteria to Produce Bioactive Compounds from Tofu Waste Using Pineapple Bromelain Enzyme - Lukman, Zulfiqar; Andrianto, Dimas; Meryandini, Anja (Bogor Agricultural University, Indonesia, 2026)
Tofu is one of the main human foodstuffs and has become an alternative substitute for animal protein. Tofu contains relatively high protein, and active compounds, but the waste produced during the tofu processing process is very abundant, namely 3.5 million tons per year in Indonesia. The production of active compounds from tofu waste can use bromelain enzymes. The bromelain enzyme in this study was produced from the fermentation of pineapple leaf waste using Pediococcus pentosaceus E7. The production of active compounds from tofu waste has not been widely reported, so this study aimed to produce active compounds from tofu waste. This study began with bromelain production, measurement of bromelain activity, bromelain precipitation, peptide production from tofu waste, Liquid Chromatography-Mass Spectrometry (LC-MS) analysis, and antibacterial testing of active compounds derived from tofu waste degradation. The results showed that the peptide content of tofu liquid waste degraded using the bromelain enzyme was 41.01±0.06 mg/mL. The LCMS results showed that 18 bioactive compounds were contained in the degradation products of tofu liquid waste. The active compounds derived from the degradation of tofu waste are capable of inhibiting the growth of Salmonella Typhimurium ATCC 14028, yielding a clear zone index of 2.53±0.12.